Influence of frequency, height and cutting time on the dry matter yield and chemical composition of Andropogon grass var. bisquamulatus - Drudi, Ary; Favoretto, Vanildo (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out at Faculdade de Ciências Agrárias e Veterinárias- UNESP. Campus de Jaboticabal, São Paulo State, Brazil, to study frequency, height and cutting time of Andropogon grass (Andropogon gayanus Kunth. var. bisquamulatus Hack.). Three cutting heights (10 cm, 20 cm and 30 cm above groud level), two cutting frequencies (35 and 42 days) and four cutting times were studied from November 1983 to March 1984. Dry matter production (total of four cuttings) was higher in plants cut less frequently (20,290 kg of dry matter/ha) and at lower heigths (10 cm and 20 cm above ground level). Plants cut more frequently showed higher protein content (9.74%) and lower crude fiber (31.83%) in comparison with those cut less frequently. Higher protein content (10.47%) was observed in the first cutting time and declined significantly in the following cuttings. Crude fiber content showed little variability (31.88% to 33.78%). In these conditions, Andropogon grass may be cut between 10cm and 20cm above ground level, from November to March and at 35 or 42-day interval, when used respectively in a rotational pasture management or in a hay production system.